Development of an adaptive coaxial concrete rheometer and rheological characterisation of fresh concrete - Josch, Sebastian; Jesinghausen, Steffen; Schmid, Hans-Joachim (Applied Rheology)
Abstract The accessibility to rheological parameters for concrete is becoming more and more relevant. This is mainly related to the constantly emerging challenges, such as not only the development of high-strength concretes is progressing very fast but also the simulation of the flow behaviour is of high importance. The main problem, however, is that the rheological characterisation of fresh concrete is not possible via commercial rheometers. The so-called concrete rheometers provide valuable relative values for comparing different concretes, but they cannot measure absolute values. Therefore, we developed an adaptive coaxial concrete rheometer (ACCR) that allows the measurement of fresh concrete with particles up to d max = 5.5 mm {d}_{{\rm{\max }}}=5.5\hspace{.5em}{\rm{mm}} . The comparison of the ACCR with a commercial rheometer showed very good agreement for selected test materials (Newtonian fluid, shear thinning fluid, suspension, and yield stress fluid), so that self-compacting concrete was subsequently measured. Since these measurements showed a very high reproducibility, the rheological properties of the fresh concrete could be determined with high accuracy. The common flow models (Bingham (B), Herschel–Bulkley, modified Bingham (MB) models) were also tested for their applicability, with the Bingham and the modified Bingham model proving to be the best suitable ones.
Keywords: Condensed Matter Physics; General Materials Science

Experimental and simulative determination and correction of the effective gap extension in structured coaxial measuring systems - Josch, Sebastian; Jesinghausen, Steffen; Dechert, Christopher; Schmid, Hans-Joachim (Rheologica Acta)
Abstract The use of structured measuring systems to prevent wall slip is a common approach to obtain absolute rheological values. Typically, only the minimum distance between the measuring surfaces is used for further calculation, implying that no flow occurs between the structural elements. But this assumption is misleading, and a gap correction is necessary. To determine the radius correction $$Δ r$$ Δ r for specific geometries, we conducted investigations on three Newtonian fluids (two silicon oils and one suspension considered to be Newtonian in the relevant shear rate range). The results show that $$Δ r$$ Δ r is not only shear- and material-independent, but geometry-dependent, providing a Newtonian flow behaviour in a similar viscosity range. Therefore, a correction value can be determined with only minute deviations in different Newtonian fluids. As the conducted laboratory measurements are very time-consuming and expensive, a CFD-approach with only very small deviations was additionally developed and compared for validation purposes. Therefore, simulation is an effective and resource-efficient alternative to the presented laboratory measurements to determine $$Δ r$$ Δ r for the correction of structured coaxial geometries even for non-Newtonian fluids in the future.
Keywords: rheology; rheometry; suspension; coaxial; correction

Instabilities of Polymer Melt Suspensions under Uniaxial Extension (Poster) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Particles as Seeds for Instabilities in Uniaxially Elongated Polymer Suspension Filaments (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

A novel correction method for the shear rate in a couette rheometer (Vortrag) - Rüther, Torben; Jesinghausen, Steffen; Schmid, Hans-Joachim
Keywords: Couette; Rheology; Correction

Innovative Werkstoffherstellung für das Polymer Laser Sintern – Teil 1 - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Jesinghausen, Steffen; Schmid, Hans-Joachim (Werkstoffe)

Innovative Werkstoffherstellung für das Polymer Laser Sintern – Teil 2 - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Jesinghausen, Steffen; Schmid, Hans-Joachim (Werkstoffe)

Instability analysis of suspensions with a polymer solution matrix (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Model droplet formation in extensional filament stretching within a Filament Extension Atomizer - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim (Rheologica Acta)
Abstract Further innovation in the field of selective laser sintering (SLS) is strongly connected to the availability of new materials since the market is dominated by polyamide 12 (>90%). The aim of this publication is to develop a descriptive model for the droplet formation process in a Filament Extension Atomizer to predict the applicability to exploit further polymers for the SLS process. The feasibility was tested, investigated and characterized using a “Dripping out of a nozzle” setup for uniaxial extension. The droplet formation process was then observed via high-speed camera imaging and classified for certain parameters. The experiments were carried out using semi-diluted polyethylene oxide (600–4000 kg/mol), glycerol and water solutions as model fluids. Driven by the Plateau-Rayleigh instability, different types of spherical droplets were observed and various droplet formation mechanisms demonstrated and analyzed. Based on the experimental results, a predictive model is derived to describe various essential parameters.
Keywords: Rheology; SLS; Lasersintering; exensional rheology

NEW CORRECTION APPROACHES FOR DETERMINING THE TRUE SHEAR RATE IN A COAXIAL-RHEOMETER (Vortrag) - Rüther, Torben; Jesinghausen, Steffen; Schmid, Hans-Joachim

Triggering instabilities of polymer solution suspensions under uniaxial extension (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Charakterisierung des Fließverhaltens von Frischbeton – Entwicklung eines adaptiven Rheometers (ACCR) und Einfluss von Maßnahmen zur Sedimentationsprävention - Pawelczyk, Sebastian; Jesinghausen, Steffen; Schmid, Hans-Joachim

Filament Extension Atomization – A novel Process for Powder Production? (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Theoretische Beschreibung des Tropfenbildungsprozesses bei der Filament Extension Atomization: Entwicklung eines Vorhersagemodells für die Tropfengröße (Poster) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Absolute Rheological Measurements of Model Suspensions: Influence and Correction of Wall Slip Prevention Measures - Pawelczyk, Sebastian; Kniepkamp, Marieluise; Jesinghausen, Steffen; Schmid, Hans-Joachim (Materials)
Since suspensions (e.g., in food, cement, or cosmetics industries) tend to show wall slip, the application of structured measuring surfaces in rheometers is widespread. Usually, for parallel-plate geometries, the tip-to-tip distance is used for calculation of absolute rheological values, which implies that there is no flow behind this distance. However, several studies show that this is not true. Therefore, the measuring gap needs to be corrected by adding the effective gap extension δ to the prescribed gap height H in order to obtain absolute rheological properties. In this paper, we determine the effective gap extension δ for different structures and fluids (Newtonian, shear thinning, and model suspensions that can be adjusted to the behavior of real fluids) and compare the corrected values to reference data. We observe that for Newtonian fluids a gap- and material-independent correction function can be derived for every measuring system, which is also applicable to suspensions, but not to shear thinning fluids. Since this relation appears to be mainly dependent on the characteristics of flow behaviour, we show that the calibration of structured measuring systems is possible with Newtonian fluids and then can be transferred to suspensions up to a certain particle content.
Keywords: wall slip prevention; effective gap height; parallel-plate system; structured surfaces; model suspensions; cement paste; fresh concrete

Interlaboratory study on rheological properties of cement pastes and reference substances: comparability of measurements performed with different rheometers and measurement geometries - Haist, Michael; Link, Julian; Nicia, David; Leinitz, Sarah; Baumert, Christian; von Bronk, Tabea; Cotardo, Dario; Eslami Pirharati, Mahmoud; Fataei, Shirin; Garrecht, Harald; Gehlen, Christoph; Hauschildt, Inga; et al. (Materials and Structures)
This paper presents the results of an interlaboratory study of the rheological properties of cement paste and ultrasound gel as reference substance. The goal was to quantify the comparability and reproducibility of measurements of the Bingham parameters yield stress and plastic viscosity when measured on one specific paste composition and one particular ultrasound gel in different laboratories using different rheometers and measurement geometries. The procedures for both in preparing the cement paste and carrying out the rheological measurements on cement paste and ultrasound gel were carefully defined for all of the study’s participants. Different conversion schemes for comparing the results obtained with the different measurement setups are presented here and critically discussed. The procedure proposed in this paper ensured a reasonable comparability of the results with a coefficient of variation for the yield stress of 27% and for the plastic viscosity of 24%, despite the individual measurement series’ having been performed in different labs with different rheometers and measurement geometries.
Keywords: Rheology; Wall Slip; Slip; apparent slip; suspension; cement; concrete

Rheo-PIV nichtkolloidaler Suspensionen: Strukturelle Untersuchungen der Strömungsentwicklung in Schlitzdüsen mit Fokus auf Wandgleiten - Jesinghausen, Steffen

Direct measurement of wall slip and slip layer thickness of non-Brownian hard-sphere suspensions in rectangular channel flows - Jesinghausen, Steffen; Weiffen, Rene; Schmid, Hans-Joachim (Experiments in Fluids)
Wall slip is a long-known phenomenon in the field of rheology. Nevertheless, the origin and the evolution are not completely clear yet. Regarding suspensions, the effect becomes even more complicated, because different mechanisms like pure slip or slip due to particle migration have to be taken into account. Furthermore, suspensions themselves show many flow anomalies and the isolation of slip is complicated. In order to develop working physical models, further insight is necessary. In this work, we measured experimentally the wall slip velocities of different highly filled suspensions in a rectangular slit die directly with respect to the particle concentration and the particle size. The slip velocities were obtained using a particle image velocimetry (PIV) system. The suspensions consisting of a castor oil–cinnamon oil blend and PMMA particles were matched in terms of refractive indexes to appear transparent. Hereby, possible optical path lengths larger than 15 mm were achieved. The slip velocities were found to be in a quadratic relation to the wall shear stress. Furthermore, the overall flow rate as well as the particle concentration has a direct influence on the slip. Concerning the shear stress, there seem to be two regions of slip with different physical characteristics. Furthermore, we estimated the slip layer thickness directly from the velocity profiles and propose a new interpretation. The PIV technique is used to investigate the viscosity and implicit the concentration profile in the slit die. It is shown that the particle migration process is quite fast.
Keywords: Rheology; Wall Slip; Slip; apparent slip; suspension